-11+9u=18u-1-14u

Simple and best practice solution for -11+9u=18u-1-14u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11+9u=18u-1-14u equation:


Simplifying
-11 + 9u = 18u + -1 + -14u

Reorder the terms:
-11 + 9u = -1 + 18u + -14u

Combine like terms: 18u + -14u = 4u
-11 + 9u = -1 + 4u

Solving
-11 + 9u = -1 + 4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-4u' to each side of the equation.
-11 + 9u + -4u = -1 + 4u + -4u

Combine like terms: 9u + -4u = 5u
-11 + 5u = -1 + 4u + -4u

Combine like terms: 4u + -4u = 0
-11 + 5u = -1 + 0
-11 + 5u = -1

Add '11' to each side of the equation.
-11 + 11 + 5u = -1 + 11

Combine like terms: -11 + 11 = 0
0 + 5u = -1 + 11
5u = -1 + 11

Combine like terms: -1 + 11 = 10
5u = 10

Divide each side by '5'.
u = 2

Simplifying
u = 2

See similar equations:

| -4+7q=8q-7-3 | | 0.5k+1.5=3 | | -4-t=-4+t | | 3x+7=7x+15 | | 15/6=n/12 | | 0.6x+2=0.7+2 | | -10-7w-10=7-4w | | 4-3cot=1 | | 40=8(x-8) | | X^2-12X-4.5=0 | | P=2x+3 | | -8y=-6-9y | | -3(5+2x)=-2x+13 | | 8-(4x-12)=8x-(3x-2) | | 2-5f=-7f+10 | | 4+2y=10-4y | | 3/5=6n | | -j=j-8 | | -5x(4x-8y^2+4)= | | 10-6n=-6-10n | | 3b-11=3+b | | 7x-14=7(x+4) | | 5+10d=9d | | 6x-(10-2x)=3x+5 | | 9b+3=22 | | 18.9125-(1/4)= | | 9b+3=20 | | 9b+3=19 | | 2x^3-11x^2-10x+75=0 | | 9b+3=18 | | 9b+3=16 | | 4(t-3)+6t=5(2t+5)-12 |

Equations solver categories